AdHealth: a feasibility study to measure digital food marketing to adolescents through Facebook. Issue 2 (3rd February 2021) - Kidd, B; Mackay, S; Swinburn, B; Lutteroth, C; Vandevijvere, S
Abstract: Objective: To test the feasibility of a browser extension to estimate the exposure of adolescents to (un)healthy food and beverage advertisements on Facebook and the persuasive techniques used to market these foods and beverages. Design: A Chrome browser extension (AdHealth) was developed to automatically collect advertisements seen by participants on their personal Facebook accounts. Information was extracted and sent to a web server by parsing the Document Object Model tree representation of Facebook web pages. Key information retrieved included the advertisement type seen and duration of each ad sighting. The WHO-Europe Nutrient Profile Model was used to classify the healthiness of products advertised as permitted (healthy) or not permitted (unhealthy) to be advertised to children. Setting: Auckland, New Zealand. Participants: Thirty-four Facebook users aged 16–18 years. Results: The browser extension retrieved 4973 advertisements from thirty-four participants, of which 204 (4 %) were food-related, accounting for 1·1 % of the exposure duration. Of those food advertisements, 98 % were classified as not permitted, and 33·7 and 31·9 %, respectively, of those featured promotional characters or premium offers. The mean rate of exposure to not permitted food was 4·8 (sd = 2·5) advertisements per hour spent on Facebook. Conclusions: Using a Chrome extension to monitor exposure to unhealthy food and beverage advertisements showed that the vast majority of advertisements were for unhealthy products, despite numerous challenges to implementation. Further efforts are needed to develop tools for use across other social media platforms and mobile devices, and policies to protect young people from digital food advertising.